Variants of concern responsible for SARS‐CoV‐2 vaccine breakthrough infections from India. Issue 4 (25th November 2021) - Singh, Urvashi B.; Rophina, Mercy; Chaudhry, Rama; Senthivel, Vigneshwar; Bala, Kiran; Bhoyar, Rahul C.; Jolly, Bani; Jamshed, Nayer; Imran, Mohamed; Gupta, Ritu; Aggarwal, Praveen; Divakar, Mohit K.; et al.
Abstract: Emerging reports of SARS‐CoV‐2 breakthrough infections entail methodical genomic surveillance for determining the efficacy of vaccines. This study elaborates genomic analysis of isolates from breakthrough infections following vaccination with AZD1222/Covishield and BBV152/Covaxin. Variants of concern B.1.617.2 and B.1.1.7 responsible for cases surge in April–May 2021 in Delhi, were the predominant lineages among breakthrough infections.